Pendampingan Pengusaha Mikro Pada Proses Pengurusan Izin Usaha Sertifikat Produksi Pangan Indistri Rumah Tangga - Masithoh, Putri; Bachtiar, Arif; Asmara, Kiky (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2023)
This article is motivated by the fact that micro, small and medium enterprises (UMKM) in Bendogerit Village, Sanan Wetan District, Blitar City are experiencing several obstacles in their development, especially in terms of business permits (NIB), home industry food production certificates (SPP-IRT) and halal certificates, so that This condition requires follow-up action, including assistance for UMKM in Bendogerit Village in arranging NIB, SPP-IRT and halal certificates. This community service is carried out using the Participatory Action Research (PAR) method. Assistance steps are carried out by conducting preliminary studies, understanding, analyzing problems, implementing actions, and evaluating implementation. This dedication resulted in findings namely; 1) UMKM players find it helpful to obtain business permits that comply with applicable regulations and social economic provisions. 2) UMKM players receive complete instructions and understanding of the process and procedures for obtaining economic business permits. 3) Obtain economic security guarantees that can be marketed in society. 4) Provide confidence to market and develop a healthy and halal economic network.